2017
DOI: 10.4055/cios.2017.9.4.529
|View full text |Cite
|
Sign up to set email alerts
|

Ischiofemoral Impingement Syndrome: Outcomes of Endoscopic Resection of the Lesser Trochanter

Abstract: Ischiofemoral impingement syndrome is a rare clinical entity characterized by chronic groin, buttock or hip pain associated with radiographic evidence of narrowing of the space between the lesser femoral trochanter and the ischial tuberosity. Introduction of magnetic resonance imaging to the clinical practice as well as the establishment of the radiological definition of the abnormal ischiofemoral distance has led to an increasing interest in this condition. Ischiofemoral impingement syndrome is a poorly under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 10 publications
(42 reference statements)
0
15
0
Order By: Relevance
“…Her seated hip flexion strength was 5-/5. The post-operative iHOT score was 85 Hernandez et al [ 12 ] 2017 Spain 4 0 2 2 6 months 43.5 42–45 Complaint of progressive, bilateral, posterior buttock pain with distal neuropathic pain radiation. On physical examination, the patient had tenderness to palpation of the ischiofemoral space and a positive long-stride walking test.…”
Section: Resultsmentioning
confidence: 99%
“…Her seated hip flexion strength was 5-/5. The post-operative iHOT score was 85 Hernandez et al [ 12 ] 2017 Spain 4 0 2 2 6 months 43.5 42–45 Complaint of progressive, bilateral, posterior buttock pain with distal neuropathic pain radiation. On physical examination, the patient had tenderness to palpation of the ischiofemoral space and a positive long-stride walking test.…”
Section: Resultsmentioning
confidence: 99%
“…1 Since then, several authors reported this type of impingement in patients who had no history of hip surgery or trauma. [10][11][12] Most studies described MRI signal change of the quadratus femoris muscle and narrowing of the ischiofemoral space on a limited number of patients. 4,6,13 Torriani et al 6 reviewed MRI of 12 hips in 9 women with posterior hip pain and abnormal MRI signal intensity of the quadratus femoris muscle.…”
Section: Discussionmentioning
confidence: 99%
“…At 2 years follow-up all patients present eda significant improvement in functional scores and in VAS, being pain free [12]. Hernandez, et al [14] described the results of 2 patients with IFIS who underwent surgery with endoscopic total resection of the lesser tuberosity using the Ilizaliturri and Camacho-Galindo [15] technique. Howse, et al [16] published an endoscopic technique similar to the technique we present.…”
Section: Discussionmentioning
confidence: 99%